Nurses' attitudes towards factors determining the safety of patients treated in pediatric departments - Malinowska-Lipień, Iwona; Sowińska, Izabela; Kocur, Sylwia; Kruszecka-Krówka, Agnieszka; Kózka, Maria; Gniadek, Agnieszka; Lompart, Łukasz; Kalemba, Urszula; Kasper, Marta; Brzostek, Tomasz (Frontiers in Health Services, 2025)
IntroductionPatient safety in healthcare is strongly influenced by safety culture, shaped by organizational beliefs, values, and effective management.Material and methodsThe study involved 434 nurses from the largest pediatric hospital in southern Poland, one of ten single-profile pediatric hospitals in the country. Data were collected using the Polish version of the Safety Attitudes Questionnaire (SAQ-SF) and a sociodemographic survey.ResultsThe highest percentage of positive responses (score ≥75) was observed in job satisfaction (56.91%) and stress recognition (53.23%). The lowest results were found in perceptions of management personnel (31.80%) and safety climate (36.41%). Stress levels negatively correlated with the number of nurses per department and shift. Lower assessments of management were associated with higher patient loads and fewer staff. Better working conditions were positively correlated with higher staffing levels.ConclusionsNurses in pediatric departments reported high job satisfaction and awareness of stress but low ratings of management and safety climate. Higher nurse staffing levels were associated with lower reported stress, indicating a relationship between staffing levels, work environment, and perceptions of patient safety.